Development Of Practicum Modules To Improve Students' Science Process Skills - Systematic Literature Review - Earlyna Sinthia Dewi; Agus Abhi Purwoko; Aliefman Hakim; I Putu Artayasa; Joni Rokhmat; AA Sukarso (International Journal of Contextual Science Education, 2025)
This study aims to systematically review how trends, approaches, and outcomes of laboratory modules can enhance students' science process skills. The review was conducted using the Systematic Literature Review (SLR) method by collecting and analyzing published research from 2015 to 2024, sourced from the Dimensions and Scopus databases. The articles reviewed were relevant, high-quality, and available in full text. To examine the relationships between keywords and research themes, the VOSviewer application was utilized. The results of the review indicate that many laboratory modules remain focused on technological aspects and feasibility testing, but few integrate design development, instrument evaluation, and field testing comprehensively. Modules designed using the ADDIE model, validated by experts, and tested through pretest–posttest methods with a control group, have proven effective in enhancing students' scientific process skills. This study provides a comprehensive overview and serves as an important foundation for developing better and more needs-appropriate practical modules.